Biogeographical and ecological insights from Australasian faunas: the megadiverse collembolan genus, Entomobrya (Entomobryidae) - Jordana, Rafael; Greenslade, Penelope (Zootaxa, 2020)
Originally the genus Entomobrya (Collembola: Entomobryidae) comprised 25 species names in Australia including 7 subspecies of which 13 were exotic (50%) and the rest native. All native species had been either described by H. Schött or H. Womersley and had not been examined since 1942. Specific characters they used were few, mainly colour pattern and gross morphological features such as unguis, unguis teeth and mucronal form. Chaetotaxic characters have now been developed. We now here recognise 47 species of Australian Entomobrya and Hymalanura based on a large collection made over 50 years. Six species (12%) are now recognised as introduced, 37 are new and three unresolved because of lack of specimens in good condition. Detailed descriptions and figures are supplied. Several new species are short-range endemics of conservation significance, others are specialised as to habitat, but most are widespread. Entomobrya is now the most species rich genus of Australian Collembola. A phylogenetic tree based on morphological and biological characters revealed clusters of exotic and montane habitat specialists, indicating that the genus is paraphyletic and so confirms other authors’ work based on molecular characters. A key is supplied to Australian genera of Entomobryomorpha. A new genus record, Himalanura, is recognised extending its range to the Southern Hemisphere and 5,000 km further southeast.